Penerapan Aplikasi Online Sistem Keuangan Desa (Siskeudes) Sebagai Variabel Intervening Guna Mewujudkan Kinerja Perangkat Nagari Dalam Pengelolaan Keuangan Di Nagari Se-Kabupaten Agam - Eko Purwanto; Edi Ariyanto (Jurnal Mirai Management, 2023)
To ensure the prosperity of the Indonesian people, it is essential to develop infrastructure and provide equal opportunities for progress in rural areas. The aim is to eliminate any remaining marginalized villages and enable rural Indonesia to compete with other advanced rural areas in terms of development and societal well-being. This research aims to examine the relationship between independent variables and dependent variables. Data will be collected through the distribution of questionnaires using a Likert scale model, which will then be tested for validity and reliability. The data analysis technique employed will be the Smart PLS method. The population for this study consists of 1,119 individuals, while the sample size will be 80 people, following Hair et al.'s recommendation. The research findings indicate that infrastructure has a positive and significant impact on performance. However, individual capacity has a negative and insignificant influence on performance. Online Siskeudes (Integrated Village Administration System) has a positive but insignificant effect on performance. Infrastructure has a positive and significant impact on Online Siskeudes, while individual capacity has a positive and significant influence on Online Siskeudes. The variable Online Siskeudes does not mediate the relationship between infrastructure and performance, and similarly, it does not mediate the relationship between individual capacity and performance